2021
DOI: 10.1039/d0ce01559h
|View full text |Cite
|
Sign up to set email alerts
|

Systematic screening forktype phase transitions – general approach and positive example for a binuclear Cu(ii) paddlewheel structure

Abstract: How to screen for k type phase transitions? Pseudo symmetry in reciprocal space represents a successful answer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…A recent CSD data-mining study revealed several low-temperature structures which undergo k -transitions into a more symmetric phase upon heating, associated with the loss or change of pseudosymmetry. 52 It seems that in multiple Z ′ > 1 crystals, including BPA, they are indeed the only thermodynamically stable forms at low temperatures and not merely “fossil relics” of the nucleation process, as generally crystallizations are carried out, instead, around room temperature, and produce mostly Z ≤ 1 structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent CSD data-mining study revealed several low-temperature structures which undergo k -transitions into a more symmetric phase upon heating, associated with the loss or change of pseudosymmetry. 52 It seems that in multiple Z ′ > 1 crystals, including BPA, they are indeed the only thermodynamically stable forms at low temperatures and not merely “fossil relics” of the nucleation process, as generally crystallizations are carried out, instead, around room temperature, and produce mostly Z ≤ 1 structures.…”
Section: Resultsmentioning
confidence: 99%
“…This journal is © The Royal Society of 2023 low-temperature structures which undergo k-transitions into a more symmetric phase upon heating, associated with the loss or change of pseudosymmetry. 52 It seems that in multiple Z′ > 1 crystals, including BPA, they are indeed the only thermodynamically stable forms at low temperatures and not merely "fossil relics" of the nucleation process, as generally crystallizations are carried out, instead, around room temperature, and produce mostly Z ≤ 1 structures. One of the parameters which can pinpoint the structural similarity between the molecules is the torsional angle (τ) formed through a carboxylic carbon and the propyl chain (C1-C2-C3-C4).…”
Section: Crystal Structure and Pseudosymmetry Meltingmentioning
confidence: 99%
“…The superior instrumentation available nowadays for diffraction experiments clearly facilitates systematic temperature-dependent studies [40], e.g., dedicated to molecular motion [41] or phase transitions [42,43] in molecular crystals. As a result of enormous progress in computer hard-and software, mobility in such molecular solids may also be assessed by theoretical methods [44,45].…”
Section: Discussionmentioning
confidence: 99%